Marker Quality Improvement in Augmented Reality Using Grey-scale Method - Dahliyusmanto; Omar, Mohd Nizam; Anggara, Devi Willieam; Hamdani, Eddy; Anto, Budhi; Isnaini, Zuli Laili (International Journal of Electrical, Energy and Power System Engineering, 2019)
Augmented Reality (AR) is a technology which combines the real world and virtual world, where users can feel the interaction between the two worlds. Marker Augmented reality or known as marker-based tracking technique uses a marker as media to display this technology. The marker is used as an object that contains images with unique patterns to identify each different object. Because it has a unique pattern, not any objects can be used as a marker. In Vuforia SDK, image recognition is done using a grayscale technique to search for angular features of the pixel image. If the image was taken directly using the camera in the old times in the form of Black and White (BNW), it has bad quality and most likely cannot be used as a marker because it has a few features. In BNW images taken directly from the camera, the Vuforia SDK detects only a few features in the image. This journal explains how the technique of making a BNW image into a marker can be detected by Augmented Reality Technology.